Juegos tradicionales y la coordinación gruesa en niños de la Institución Educativa Inicial N° 333 Cushillo Cocha Ramón Castilla 2025 - Sampayo Candido, Eglin Dorote (2025)
The present research aimed to determine the relationship between traditional games and the level of gross coordination development in children at the Initial Educational Institution No. 333 Cushillo Cocha Ramón Castilla 2025. The study was developed using a quantitative approach, with a basic correlational design. The sample consisted of 82 children from the initial level. For data collection, the observation technique was used, using a guide validated by expert judgment. The results showed a correlation coefficient of 0.577, indicating that the greater the participation in traditional games, the greater the development of gross coordination in children. The significance of 0.05 allowed us to reject the null hypothesis, confirming the existence of a significant and positive relationship between the variables, which ratifies that traditional games have a favorable impact on children's motor development. This finding underscores the importance of traditional games as an essential tool for promoting the development of gross motor skills in children in the preschool level at Cushillo Cocha Early Childhood Education Institution No. 333.